Удмурт калыклы гожтэт - Грязев Георгий Геннадьевич (Удмуртия, 2020)
Экземпляры: СБ (20210514) / Инвентарный номер: 61028 / Цена: 324.00 / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: У 30 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)